Isolation and characterization of drought responsive EcDehydrin7 gene from finger millet (Eleusine coracana (L.) Gaertn.) - Singh, Rajiv Kumar; Phanindra, Mullapudi Lakshmi Venkata; Singh, Vivek Kumar; Sonam, Sonam; Raghavendrarao, Sanagala; Solanke, Amolkumar U.; Kumar, Polumetla Ananda (The Indian Journal of Genetics and Plant Breeding, 2016)
Finger millet is known for its drought tolerance ability. The present investigation was carried out to explore drought responsive genes from finger millet. To generate more genetic and genomic information, a highly normalized cDNA library was prepared from 12 days old stress imposed seedlings and utilized it for identification of drought responsive genes using cDNA macroarray. Differentially expressing six genes (Dehydrin7, Hypothetical protein1,Chloroplast envelope membrane protein, HypotheticalÂ protein2, S-adenosyl methionine decarboxylase2 and unknown gene) were selected for qRT-PCR analysis under different stress conditions. Gene EcDehydrin7 (Accession No. KM096446) showed high expression under drought and heat stress. Functional validation of this gene can provide more information about drought tolerance mechanism in crop plants.